Hemophagocytic lymphohistiocytosis secondary to AIDS-related histoplasmosis and visceral leishmaniasis. (August 2022) - Tomaino, María V; Barletta, José AE; Andreani, Mariana; Sisto, Alicia; Abusamra, Lorena; Guelfand, Liliana; Rolón, María J
Hemophagocytic Lymphohistiocytosis (HLH) is a rare, highly aggressive syndrome involving dysregulated immune response. Most cases are secondary to underlying diseases including infections, autoimmune disorders and malignancies. The burden of disease of histoplasmosis and leishmaniosis associated with advanced HIV is still significant in low-and-middle income countries (LMIC). We present a case of histoplasmosis and leishmaniasis associated HLH in a man with an AIDS diagnosis.